2017
DOI: 10.1016/j.artd.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection and transfusion rates are higher in underweight total knee arthroplasty patients

Abstract: BackgroundUnderweight (UW) patients undergoing total hip arthroplasty have exhibited higher complication rates, including infection and transfusion. No study to our knowledge has evaluated UW total knee arthroplasty (TKA) patients. We, therefore, conducted a study to investigate if these patients are at increased risk for complications, including infection and transfusion.MethodsA case-control study was conducted using a prospectively collected institutional database. Twenty-seven TKA patients were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Although allogeneic blood transfusions are restricted to reduce the adverse effects of blood transfusion in most cases, the risks include perioperative joint infection, systemic infection, internal organ damage, prolonged hospital stay, venous thromboembolic events, and mortality . Immunologically, allogeneic blood transfusions generally cause up regulation of humoral immunity and down regulation of macrophage and T‐cell immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although allogeneic blood transfusions are restricted to reduce the adverse effects of blood transfusion in most cases, the risks include perioperative joint infection, systemic infection, internal organ damage, prolonged hospital stay, venous thromboembolic events, and mortality . Immunologically, allogeneic blood transfusions generally cause up regulation of humoral immunity and down regulation of macrophage and T‐cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In this nationally representative study of patterns of transfusion use in hip arthroplasty, we observed significantly high rates of blood transfusion among patients undergoing hip arthroplasties regardless of risk factors including patient, hospitals, and other characteristics, compared with studies in other countries . Furthermore, this study is the first of its kind to estimate the economic burden of transfusion associated with hip arthroplasty in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of underdosing becomes even more important when one considers the fact that the majority of patients not receiving an adequate dose of vancomycin were obese and those overdosed were likely to be underweight patients. Obese patients are at higher risk of PJI in the first instance [15,25] and depriving them of adequate perioperative antibiotic prophylaxis may have an additional adverse effect on the rate of PJI. It is also possible that the signal of increased PJI observed in obese patients may in part be a result of inadequate perioperative antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…When soft tissue repair was performed during surgery, the soft tissue area of the transplant was not sufficient to completely repair the defective tissue, resulting in a large range of artificial tibial prostheses directly under the skin. Artificial prostheses that lost soft tissue cushioning might cause late-onset infection during later rehabilitation training and exercise [22,23].…”
Section: Discussionmentioning
confidence: 99%